Dehydroepiandrosterone (DHEA) and DHEA-sulfate (DHEAS) protect hippocampal neurons against excitatory amino acid-induced neurotoxicity - Kimonides, V. G. (National Academy of Sciences, 1998)
DHEA, together with DHEAS, is the most abundant steroid in the blood of young adult humans. Levels in humans decline with age and during certain types of illness or stress. We have found that DHEA(S) can prevent or reduce the neurotoxic actions in the hippocampus of the glutamate agonists N-methyl-d-aspartic acid (NMDA) both in vitro and in vivo or α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and kainic acid in vitro. Pre-treatment with DHEA (10–100 nM for 6–8 h) protected primary hippocampal cultures from embryonic day 18 (E18) embryos against NMDA-induced toxicity (0.1, 1, 10, and 50 mM). DHEA added either with NMDA (1 mM) or 1 h later had lesser, but still significant, protective actions. DHEAS also reduced NMDA-induced toxicity (1 mM), although the lowest effective dose of DHEAS (100 nM) was higher than that of DHEA (10 nM). DHEA (100 nM) protected cultured neurons against the neurotoxic actions of either AMPA (25 μM) or kainic acid (1 mM) as well. In vivo, s.c. pellets of DHEA, which resulted in plasma levels that resembled those in young adult humans, protected hippocampal CA1/2 neurons against unilateral infusions of 5 or 10 nmol of NMDA. Because the release of glutamate has been implicated in the neural damage after cerebral ischemia and other neural insults, these results suggest that decreased DHEA levels may contribute significantly to the increased vulnerability of the aging or stressed human brain to such damage.